Carved in history an educational cultural complex promoting Betis' Woodcarving Industry - Vergara, Roxanne Mariel C.; Navarra, Nappy L. (Quezon City College of Architecture, University of the Philippines Diliman, 2015)
The district of Betis, which is located in Guagua, Pampanga, is famous for its community of woodcarvers who are skilled in crafting furniture and sculptures. This industry is a tradition that goes back even during the pre-colonial era, and it is a source of pride for the locals of Guagua. However, even if this industry is a part of Guagua's culture, the locals do not feel a deep connection to it because they know very little about other details about woodcarving like its history or how these products are made. As a result, the community feels detached to this piece of heritage. Therefore, the study aims to devise a method of educating the woodcarving industry to the community via design solutions in landscape architecture. First, the researcher better understood how the community felt about this industry from conducting surveys and even learned about what specific information they are interested in learning. The researcher also interviewed local woodcarvers who gave their input on how they carved their creations and what spaces they required to do their work. The result of data gathering was vital information on the needs of both the woodcarvers and the community, which then led to specifically the inclusion and layout of certain spaces that would benefit the needs of these users.
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Woodcarving -- Guagua (Pampanga)